UV irradiation and infrared observation of sulfur dioxide clusters and solids at cryogenic temperature - Ito, Fumiyuki; Koga, Ryoichi; Negishi, Shohei; Hirahara, Yasuhiro (Chemical physics letters, 2023)
[Display omitted] •UV irradiation of clusters/solids of SO2 produces SO3 (self-oxidation)•The production of SO3 with UV below the dissociation limit indicates a concerted reaction.•Observed spectral features are reproduced by DFTB calculations combined with minima-hopping algorism. Clusters in the Ar matrix and solids of sulfur dioxide (SO2) produced at cryogenic temperature have been subject to UV irradiation, followed by spectroscopic observation in the mid-infrared region. We found that UV irradiation in the B-band (266–300 nm) of SO2 resulted in annealing and production of sulfur trioxide (SO3) even below the dissociation limit of SO2. Other sulfur oxides such as SO and S2O2 have not been detected. Observed infrared spectra have been successfully compared with theoretical simulations for global minima of (SO2)n (n = 2–10) obtained by the minima hopping method combined with density functional tight-binding (DFTB) method.